Performance evaluation of water-swelling and oil-swelling elastomers. (October 2016) - Qamar, Sayyad Zahid; Pervez, Tasneem; Akhtar, Maaz
Swelling elastomers are special polymers that increase in volume when exposed to water or oil. They have been successfully deployed in oil and gas wells for isolation of water-producing zones, partial replacement of cementing, slimming down of wells, and so on. Performance appraisal and design modifications cannot be attempted without knowledge of material response under specific field conditions. Results from an experimental investigation are presented here about the behavior of two commercial elastomers, one water swelling and one oil swelling. Of the one-month total testing time, one set of samples (for each elastomer type) was tested under acid for one day, and the other set without any acid exposure. Readings were taken at different stages of swelling to record the variation in volume, thickness, and hardness of elastomer samples. Test parameters were set to match existing conditions in a regional oil well. These results can be used to assess performance of elastomers under given well conditions and for modeling and simulation of seal behavior.